Leptospirosis in an Urban Setting: Cases Diagnosed at a Private Medical Center of Western Colombia, 2008-2012† - M. Ramirez-Ramirez, Maria; M. Leon-Castaneda, Olga; J. Rodriguez-Morales, Alfonso (Recent Patents on Anti-Infective Drug Discovery, 2015)
Introduction: Leptospirosis has reemerged as significant threat particularly in developing countries, including those in Latin America. Data from Colombia is still limited and there are no published studies in the Western area of the country. Methods: Data on suspected cases were collected over the study period (2008- 2012). Cases were diagnosed clinically and confirmed by ELISA IgG and microscopic agglutination test (MAT) (titers ≥1:400). Results: During the study period 264 suspected cases of leptospirosis were found. From those, 8.33% (22 cases) were microbiologically confirmed. Number of suspected cases increased in the period from 20 (2008) (40 cases/100,000 consultations) to 58 (2012) (120 cases/100,000 consultations). Regard sex distribution, 62.5% were males, 14% in the age group 21-30 y-old, from confirmed cases 95% live in urban areas of Pereira, 25.7% own dogs and 13.2% cats, 32.3% reporting rats at home as well 22.7% at work places. From confirmed cases 72.7% were hospitalized. Clinical findings found were: fever (60.2%), myalgias (47%), and headache (41.9%), among others. All the cases corresponded to Leptospira interrogans. Regard the serovars, in these patients 6 were identified: Australis (54.5%), Icterohaemorrhagiae (45.5%), Canicola (45.5%), Panama (45.5%), Pomona (36.3) and Grippotyphosa (1%). Thirty nine percent of the patients received antimicrobial therapy, 50% ceftriaxone. No deaths occurred. Conclusion: Leptospirosis is an emerging infectious disease that has changed from an occupational disease of veterinarians, farmers, butchers, and other animal handlers to a cause of epidemics in poor and decayed urban communities in developing countries, including those in Latin America such as Colombia.
Keywords: epidemiology